Customer satisfaction regarding the service quality of the foreign exchange department of Mercantile Bank Limited, Mirpur Branch - Siddika, Ayesha (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2014.